Effect of alcohol dosage on long‐term outcomes after alcohol septal ablation in patients with hypertrophic cardiomyopathy. Issue 6 (4th March 2016) - Liebregts, Max; Vriesendorp, Pieter A.; Steggerda, Robbert C.; Schinkel, Arend F.L.; Balt, Jippe C.; Ten Cate, Folkert J.; Michels, Michelle; Ten Berg, Jurriën M.
Abstract : Objectives: The aim of this study is to assess the long‐term effects of alcohol dosage in alcohol septal ablation (ASA) on mortality and adverse arrhythmic events (AAE). Background: ASA can be performed to reduce left ventricular outflow tract (LVOT) obstruction in patients with hypertrophic cardiomyopathy (HCM). However, the effect of alcohol dosage on long‐term outcomes is unknown. Methods: This retrospective cohort study includes 296 HCM patients (age 60 ± 22 years, 58% male) who underwent ASA because of symptomatic LVOT obstruction. Twenty‐nine patients (9.8%) were excluded because the alcohol dosage could not be retrieved. Primary endpoints were all‐cause mortality and AAE. Results: During 6.3 ± 3.7 years of follow‐up, all‐cause mortality and AAE rates were similar in patients who received ≤2.0 mL ( n = 142) and >2.0 mL ( n = 121) alcohol during ASA. Age was the only independent predictor of mortality (HR 1.1 95% CI 1.0–1.1, P < 0.001). Predictors of AAE were maximum CK‐MB >240 U/L (HR 3.3 95% CI 1.5–7.2, P = 0.003), and sudden cardiac death survivor (HR 5.9 95% CI 1.7–20.3, P = 0.004). There was a mild to moderate correlation between CK‐MB levels and amount of alcohol (Spearman's ρ 0.39, P < 0.001), cross‐sectional area of the target septal branch ostium/ostia (Spearman's ρ 0.19, P = 0.003), and maximum ventricular wall thickness (Spearman's ρ 0.17, P = 0.006). Conclusions: Alcohol dosage appears not to have a long‐term effect on mortality and AAE. A larger infarct size created by ASA increases the risk of AAE, and extended monitoring of these patients is advised. © 2016 Wiley Periodicals, Inc.